2010
DOI: 10.5713/ajas.2010.90448
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Dietary Organic Selenium Supplement at Different Dietary Protein Concentrations on Growth Performance, Body Composition and Antioxidative Status of Broilers Reared under Heat Stress

Abstract: Three hundred chicks were randomly assigned among four treatments to evaluate the effect of an organic selenium supplement at various levels of dietary protein. Two levels of supplemental selenium (0 and 0.3 mg/kg) from zinc-L-selenomethionine were tested at two levels of dietary protein (normal and reduced) in a completely randomized design with 2×2 factorial layout. The experiment lasted up to 49 d of age during which all birds were exposed to 31±1°C. The effects of selenium or its interaction with CP on gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…However, both SY and SN were more effective than SS in the reduction of abdominal fat. Similarly, Khajali et al (2010) found a decreased abdominal fat yield in broilers that treated with a dietary addition of 0.3 mg/kg of Se from an organic origin. Safdari-Rostamabad et al (2017) also reported lower liver and abdominal fat yields in broilers receiving 0.6 or 1.2 mg/kg of Se in the form of SN in comparison with those fed a control diet.…”
Section: Discussionmentioning
confidence: 75%
“…However, both SY and SN were more effective than SS in the reduction of abdominal fat. Similarly, Khajali et al (2010) found a decreased abdominal fat yield in broilers that treated with a dietary addition of 0.3 mg/kg of Se from an organic origin. Safdari-Rostamabad et al (2017) also reported lower liver and abdominal fat yields in broilers receiving 0.6 or 1.2 mg/kg of Se in the form of SN in comparison with those fed a control diet.…”
Section: Discussionmentioning
confidence: 75%
“…These forms include, but not limited to Se enriched yeast strains [41], Se enriched malt [42], garlic, cabbage [43], Chlorella algae [44], B-Traxim Se [45] and 2-hydroxy-4-methylselenobutanoic acid [46]. In the present study, added Se was in the form of a Se chelate more specifically ZnSeMet which is a levo-isomer of selenomethionine that is also chelated with an atom of Zn [47,48]. Previous work with ZnSeMet indicated differences compared to other forms of organo-Se compound, more specifically to pure Se-Met and Se yeast, related to better solubility, stability and availability [47,49,50].…”
Section: Discussionmentioning
confidence: 94%
“…So far, the potential enhancement of antioxidant ability from organic Se sources has been applied to alleviate the negative effect on poultry production when this is subjected to environmental stress challenge (45,46). For example, many studies in broilers showed that the dosage of Se, added at a range of 0.3-1.0 mg/kg to the diet, improved the growth performance of chicken and quails when exposed to heat stress, contributing to the improvement of immune function and the increased activities of glutathione, GSH-Px, and SOD (47)(48)(49)(50)(51)(52)(53). It is also implied that a greater amount of Se is required for enhancing selenium-dependent antioxidant enzyme activities and gene expression relative to the glutathione system to alleviate oxidative damage induced by heat stress in poultry (54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%